USING PALEMBANG’S TRADITIONAL FOODS AS ENGLISH TEACHING MATERIALS: A THEME-BASED LANGUAGE INSTRUCTION - Nurul Aryanti (Politeknik Negeri Sriwijaya, 2010)
This paper is aimed at discussing the use of Palembang’s traditional foods as teaching material through a theme-based language instruction. This idea is based on the awareness of the writer to maintain and preserve their cultures, especially in terms of foods. The data are got by reading references related to the subject, interviews, and observations. The data shown that the Palembang’s indigenous foods can support Palembang as a cultural hub, because the great number of the foods are well-known and spread not only in local but also national scope. Teachers of English can participate in maintaining and preserving the foods by using the foods as teaching material. This can be done through theme-based language instruction. This approach is stressed on the real-life situation that are genuinely communicative and it tends to integrate the four language skills naturally.